2021
DOI: 10.1371/journal.pone.0249030
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic goal adapted task oriented dialogue agent

Abstract: Purpose Existing virtual agents (VAs) present in dialogue systems are either information retrieval based or static goal-driven. However, in real-world situations, end-users might not have a known and fixed goal beforehand for the task, i.e., they may upgrade/downgrade/update their goal components in real-time to maximize their utility values. Existing VAs are unable to handle such dynamic goal-oriented situations. Methodology Due to the absence of any related dialogue dataset where such choice deviations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Then recently, the research [ 28 ] proposes a personalized end-to-end task-oriented conversation system that uses a memory network to create attractive and persona-consistent replies. In other recent publications [ 29 32 ], the researchers emphasized the DST module to carry out persuasion in task-oriented conversation agents to catch and address dynamic user needs effectively.…”
Section: Related Workmentioning
confidence: 99%
“…Then recently, the research [ 28 ] proposes a personalized end-to-end task-oriented conversation system that uses a memory network to create attractive and persona-consistent replies. In other recent publications [ 29 32 ], the researchers emphasized the DST module to carry out persuasion in task-oriented conversation agents to catch and address dynamic user needs effectively.…”
Section: Related Workmentioning
confidence: 99%
“…• VIRAAL-The study [109] • Sub-modularity-inspired data ranking function -The study [110] tries to address the problems for small domains, which requires a huge amount of domain-related training data. The data selection technique is proposed in a low-data regime that enables with fewer labelled data.…”
Section: Rq4 Which Techniques Are Effective For Reducing the Need For...mentioning
confidence: 99%
“…Prior research initially focused on BERT ( Devlin et al, 2019 ) for dialogue state tracking, intent classification, and response generation (e.g., Dong et al, 2019 ; Tiwari et al, 2021 ) primarily in task-oriented dialogue, which is designed for a specific goal, such as restaurant booking. Recently, LLMs (e.g., GPT-3 ( Brown et al, 2020 ), LLaMA ( Touvron et al, 2023 ), Falcon ( Penedo et al, 2023 ), Pythia ( Biderman et al, 2023 ), Mistral ( Jiang et al, 2023 )) that are trained on vast amounts of textual data, showed promise for generating coherent text and speech by using prompts for inferring the context, thereby, enabling open-domain dialogue with unrestricted topics ( Huang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%